Influence of Bulb Size and GA3 on Bulb and Bulblets Production of Tuberose - Choudhury, S.; Amin, M. R.; Uddin, A. K. M.; Uddain, J. (International Journal of Bio-resource and Stress Management, 2010)
The experiment was conducted at horticulture farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh to study the influence of bulb size and different levels of GA3 on bulb and bulblets production of tuberose during the period of April 2006 to January 2007. The two factors experiment was laid out with Randomized Complete Block Design (RCBD) with 3 replications. Factor A: Three sizes of bulb, i.e. small (1-1.5 cm), medium (>1.5-2.0 cm) and large (>2.0-2.5 cm) and Factor B: Six levels of GA3 (0, 100,150, 200, 250 and 300 ppm). In case of bulb size, maximum weight of individual bulb (45.48 g), maximum number of bulblets plant-1 (14), and maximum yield of bulb (9.10 t ha-1) and bulblets (11.44 t ha-1) was recorded in large size bulb as compared to other sizes of bulb. The highest yield of bulb (8.76 t ha-1) and bulblets (12.14 t ha-1) was found in 300 ppm concentration GA3.